Trailing the Bolsheviki : Twelve Thousand Miles with the Allies in Siberia - Ackerman, Carl W. (Carl William), 1890-1970 (Book collections on Project MUSE., 2020)
"American journalist Carl W. Ackerman's account of his experience as a New York Times special correspondent in Siberia and the Far East during the Russian Civil War"--